Analysis of Marketing Strategy, Purchasing Interest and Loyalty Towards Retail Stores’ Profitability in Bekasi Area - Andrian, Andrian; Nila Sari, Pratiwi; Anwar, Misbahul; Wijayaningsih, Rini; Wahyu Putra, Ch. Indra (CV. Era Digital Nusantara, 2025)
This study investigates the influence of marketing strategy, purchasing interest, and consumer loyalty on the profitability of retail stores in Bekasi Area. In a highly competitive market, retail businesses must implement effective marketing strategies to attract consumers and foster long-term loyalty. There are 178 customers who frequently shop at retail stores, including retail business managers. By using a quantitative approach, the research employs survey data collected from retail consumers and analyzes the relationships between variables through path analysis. The findings reveal that marketing strategies—particularly those involving pricing, promotion, store location, and customer service—significantly affect both purchasing interest and consumer loyalty. Furthermore, consumer loyalty plays a crucial role in enhancing profitability through repeat purchases and positive word-of-mouth. This study shows that 36.4% of purchasing decisions can be explained by the independent variables of Marketing Strategy, Purchasing Interest and Consumer Loyalty, while the remaining 63.6% is explained by other causes outside the variables in this study, like Consumers’ Satisfaction, Repurchase Intention and so on. The study concludes that integrated marketing efforts and loyalty-building initiatives are essential for sustaining profitability in the Indonesian retail sector.